Energy and Economic Evaluation of Retrofit Actions on an Existing Historical Building in the South of Italy by Using a Dynamic Simulation Software. (November 2015) - Ciampi, Giovanni; Rosato, Antonio; Scorpio, Michelangelo; Sibilio, Sergio
Abstract: In this paper the performance of the following retrofit actions on an existing historical public building were dynamically simulated by using the simulation software TRNSYS: a) utilization of thermostats for indoor air temperature control with 20 °C and 18 °C as target temperatures; b) increment of current thermal insulation of opaque walls and windows; c) replacement of the current diesel-fired boiler with a natural gas-fired condensing boiler. The simulation results were analyzed from both energy and economic point of views in order to assess their energy saving potential and economic suitability.